Concepts for point-of-care ultrasound training in low resource settings: a scoping review - Eppel, Friedrich; Hunstig, Friederike; Bélard, Sabine; Kreuels, Benno (The Ultrasound Journal, 2025)
Background: Point-of-care ultrasound (POCUS) is a potent diagnostic tool especially in resource-limited settings. The implementation of POCUS diagnostics requires adequate training of POCUS operators. This scoping review aimed to identify and describe POCUS training concepts that have been applied in low-and middle-income countries (LMICs). Methods and findings: All studies on diagnostic POCUS training in LMICs that could be found in the Cochrane, Embase, Google Scholar, and Medline databases up to July 6, 2023, were included and data was extracted for descriptive analysis. The review protocol was registered at OSF https:// doi. org/ 10. 17605/ OSF. IO/ 8FQJW. A total of 53 publications were included with 59% of studies (n = 31) conducted in Africa and 23% (n = 12) in Asia. The majority of studies (n = 41, 81%) described short courses amongst which 40% were one-off sessions and 60% described longitudinal trainings. Curricula were mostly related to emergency medicine and obstetrics and organ-focused protocols (lung n = 29 (54%), cardiac n = 28 (53%), obstetric n = 23 (43%)). Trainees were largely medical doctors and clinical officers with minimal or absent ultrasound skills. Training challenges included resource constraints and lack of context adaptation. Best practice recommendations included focus on hands-on training, low trainer to trainee ratio, protected training time, online training options, use of local trainers, short and concise training manuals in print, continuous supervision and early and on-going evaluation, as well as tele-mentoring. Conclusions: Context integration and focus on local needs, trainer availability and suitability, durable equipment and maintenance, as well as emphasis on hands on training including patients with relevant pathology, were key aspects for targeted and sustainable POCUS training in LMICs identified in this review.